In Maithilisharan Gupt's Saket, Urmila Acts as A Visible Character: An exploration of Urmila's role in Maithilisharan Gupt's 'Saket' (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The national poet of India, Maithilisharan Gupt (1886-1964), penned the 1931 literarymasterpiece 'Saket' in the Indian language of Hindi. Saket is an outstanding poem with connections tothe Ramayana, the greatest holy epic. It focuses on Ramayana figures. There are a total of 12 cantos, butthe one that focuses on Urmila, the wife of Lakshman, stands out. 'Saket' may be translated literally asAyodhya city. Gupt's 'Saket' tells the story of the Ramayana through Lakshman's perspective. It iscomposed of dwipaada. The work is wonderful because of the vivid imagery and the depth it delves intothe feelings of characters who were not given enough time to develop in the Ramayana's main tale. Itadds more dimensions to the Ram's Tale adventure. This study considers the value of Urmila'spersonality in helping her husband keep his word to his brother about enlisting in the military. SearchTerms Saket, Exploration, Dwipadda, Story, Magnificent.